A crise do sindicalismo e o caso do Sindicato APEOC: uma análise a partir da greve de 2011 - Pessoa, Márcio Kleber Morais (2015)
This Master’s dissertation general goal is to discuss the contemporary labor union crisis, having as empirical focus the relationship between teachers from the state of Ceará and their representative entity, the APEOC union, covering the period from the 2011 strike until now. This discussion will seek to elucidate the consequences of that strike on the relationship between the grass roots and the union leaders, given that that movement was ended leaving tensions between the related subjects. To carry out this research, the chosen empirical field consists of the interactions environments between the grass roots and the union leaders, just as: demonstrations, general assemblies and others. Moreover, data was collected in two schools from the state of Ceará: one in the capital, Fortaleza, and another in the interior. The goal is to understand these subjects’ visions on the role of their labor union in the analyzed period. The field research in the school of the capital occurred between February and May of 2014. In the interior one, the investigation occurred between July and December of the same year. The dissertation text presents the narrative of the strike, from social dramas methodological resources, following Victor Turner’s formulations, the analysis of elements of tension and conflicts between the parts during and after the strike movement and the position of interviewed teachers from the two schools chosen as empirical field. Some of the results founded out were: the 2011 strike has generated conflicts between the union leaders and the grass roots; these conflicts reveal processes of oligarchization, bureaucratization and relative nationalization of APEOC union, that foster its representativeness crisis, demobilizing the grass roots. Furthermore, the teaching staff perceived in their profession what Graça Druck names dismantling, what was confirmed by the analysis of laws related to the activity, besides how the Plan of Posts, Careers and Salaries was restructured after 2011. The dissertation concluded that the dismantling appears as a way of fragmentation of the category when it sprays teacher’s demands, what is enhanced by its intern fragmentation, namely, by the category’s intern conflicts related to the way the 2011 strike was ended.